The Hamburg Online Math Test MINTFIT for Prospective Students of STEM Degree Programmes - Barbas, Helena; Schramm, Thomas (MSOR Connections, 2018)
MINTFIT is a joint project of the HafenCity University Hamburg (HCU), Hamburg University of Applied Sciences HAW), Hamburg University of Technology (TUHH) and Universität Hamburg (UHH) together with the Hamburg Ministry of Science, Research and Equalities (Behörde für Wissenschaft, Forschung und Gleichstellung, BWFG) to support high school students and others interested in STEM studies. The MINTFIT Math Test is a diagnostic online test which gives its participants the opportunity to check if their math skills are sufficient for a successful start into the first terms of a STEM degree programme.